2012
DOI: 10.1007/s00265-012-1383-7
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: a comparative study of migratory behavior in social amoebae

Abstract: Social amoebae aggregate to form a multicellular slug that migrates some distance. Most species produce a stalk during migration, but some do not. We show that D. giganteum, a species that produces stalk during migration, is able to traverse small gaps and utilize bacterial resources following gap traversal by shedding live cells. In contrast, we found D. discoideum, a species that does not produce stalk during migration, can traverse gaps only when in the presence of other species' stalks, or other thin filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…If stalk height is crucial for dispersal, as suggested previously (Smith et al, 2014), then strains that allocate fewer cells to the stalk might experience trade-offs between the immediate benefits of producing more spores by reducing stalk allocation and the ability to disperse those spores to new locations. Although the phylogenetic conservation of the stalk across dictyostelids suggests that dispersal is probably an important fitness component in this organism, a caveat to this interpretation is that the stalk may serve a different function in other dictyostelid species, especially those that produce extensive, nonupright stalks of indeterminate size, for example, by helping the migratory slug to bridge gaps in the soil (Gilbert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If stalk height is crucial for dispersal, as suggested previously (Smith et al, 2014), then strains that allocate fewer cells to the stalk might experience trade-offs between the immediate benefits of producing more spores by reducing stalk allocation and the ability to disperse those spores to new locations. Although the phylogenetic conservation of the stalk across dictyostelids suggests that dispersal is probably an important fitness component in this organism, a caveat to this interpretation is that the stalk may serve a different function in other dictyostelid species, especially those that produce extensive, nonupright stalks of indeterminate size, for example, by helping the migratory slug to bridge gaps in the soil (Gilbert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the explanations for the variation in these features are not known, although several studies provide information about some of the potential functions of the stalk. For example, spores that sat atop stalks were more likely to be picked up by an insect vector (smith, Queller, and Strassman 2014), and stalks emanating from the rear of the slug can help in traversing gaps in the soil (Gilbert et al 2012)-yet, whether and how these features are used in nature remains to be seen. In addition, while some stalk features may provide a fitness advantage, there may also be functional constraints imposed by development or physics.…”
Section: Discussionmentioning
confidence: 99%
“…That the stalk might serve a different or additional purpose in different dictyostelids was proposed by Bonner (1982) and later tested by Gilbert et al (2012). They showed that the stalked migrator D. giganteum could use its stalk as a bridge to traverse small gaps in the substratum.…”
Section: Stalked Migrationmentioning
confidence: 99%
“…; Gilbert et al. ). Most studies of kin discrimination have focused on this species, but understanding species level discrimination and discrimination in other species puts the work on D. discoideum in context.…”
mentioning
confidence: 99%